ANALYSIS OF WORKING CAPITAL AND FINANCIAL PERFORMANCE OF SHARIA BANKING INDUSTRY INMANDIRI SYARIAH BANK JAMBI - Sumantri, Sumantri; Albetris, Albetris (Dinasti Publisher, 2020)
The purpose of this study is to find out working capital in an independent Islamic bank, the financial performance of an independent Islamic bank in Jambi by using a liquidity ratio analysis tool (current ratio, cash ratio) and profitability ratio (profit margin) and there is also a significant relationship between current ratio cash ratios and profit margins with working capital at the Islamic bank Mandiri jambi. The analytical tool used is multiple linear regression. Study the significant relationship between current ratio (X1), cash ratio (X2) profit margin (X3) as the independent variable and working capital as the dependent variable. The results of working capital analysis at the jambi independent Islamic bank have fixed assets and current assets with a total average current assets from 2016 to 2019 of Rp 88,919,015.5 and for average fixed assets from 2016 to 2019 of IDR 856,841.06. Analysis results Financial performance through liquidity ratios namely current ratio and cash ratio obtained an average current ratio from 2016 to 2019 of 115.67%, and obtained an average cash ratio from 2016 to 2019 of 1.55%. For profitability ratios namely profit margins can be obtained an average profit margin from 2016 to 2019 of 72.82% with very good criteria because it exceeds the maximum limit of the standard ratio. The test results on the relationship of the current ratio, cash ratio and profit margin with working capital obtained a person correlation current ratio of 1,000 means perfect correlation and there is a relationship between the current ratio with working capital. For cash ratio with a person correlation value of cash ratio of 1,000 means perfect correlation and there is a relationship between cash ratio and working capital. For the value of person correlation margin of 1,000 means that it means perfect correlation and there is a relationship between profit margin and working capital. It can be concluded that working capital influences the current ratio, cash ratio and profit margin.